2020
DOI: 10.1038/s41467-020-16796-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-mediated apoptosis eliminates aneuploid cells in a mouse model of chromosome mosaicism

Abstract: The high incidence of aneuploidy in the embryo is considered the principal cause for low human fecundity. However, the prevalence of aneuploidy dramatically declines as pregnancy progresses, with the steepest drop occurring as the embryo completes implantation. Despite the fact that the plasticity of the embryo in dealing with aneuploidy is fundamental to normal development, the mechanisms responsible for eliminating aneuploid cells are unclear. Here, using a mouse model of chromosome mosaicism, we show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
114
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 57 publications
12
114
0
3
Order By: Relevance
“…3g, h). This result could also be explained by selective elimination of the aneuploid cells by programmed cell death as the embryo developed beyond day 5, as previously shown to occur in mouse embryos 26,30 . Alternatively, if the aneuploid cells were restricted to the mural trophoblast these cells could have been removed during the biopsy procedure at day 5.…”
Section: (Supplementarysupporting
confidence: 53%
See 1 more Smart Citation
“…3g, h). This result could also be explained by selective elimination of the aneuploid cells by programmed cell death as the embryo developed beyond day 5, as previously shown to occur in mouse embryos 26,30 . Alternatively, if the aneuploid cells were restricted to the mural trophoblast these cells could have been removed during the biopsy procedure at day 5.…”
Section: (Supplementarysupporting
confidence: 53%
“…In this regard, the fate of aneuploid cells in mosaic human embryos remains unknown. Previous results from our lab have shown that in mouse embryos aneuploid cells in the embryonic epiblast present a higher rate of apoptosis than aneuploid cells in the extra-embryonic tissues 26,30 . These results rely on inducing aneuploidy by the drug reversine, which can cause chaotic aneuploidies 26 .…”
Section: Discussionmentioning
confidence: 67%
“…They found that aneuploid cells in the fetal lineage (i.e., inner cell mass producing the fetus) were eliminated by apoptosis, while those in the placental lineage (i.e., the TE) did show proliferative defects though survived. In a recently published study from the same group, Singla et al [18] have demonstrated that aneuploid cells are preferentially eliminated from the embryonic lineage in a p53-dependent process involving both autophagy and apoptosis before, during and after implantation. It might be therefore argued, that early embryos development could be controlled by the establishment of a cell death program to ensure the elimination of damaged cells [19], while maintaining an optimal balance between survival and apoptotic signals.…”
Section: Introductionmentioning
confidence: 99%
“…A mouse model demonstrated that aneuploid cells can be eliminated during embryo development either via apoptosis in inner cell mass or a prolonged cell cycle in trophectoderm cells (Bolton et al 2016). Apoptosis of aneuploid cells in mouse embryos is linked with autophagy-mediated pathways; however, whether the same 'rescue' mechanisms operate in human embryos remains to be determined (Singla et al 2020).…”
Section: Consequence Of Chromosomal Mosaicism On Embryo Developmentmentioning
confidence: 99%
“…Understanding the fate and effect of aneuploid cells in an environment of euploid cells during preimplantation development (Bolton et al 2016, Singla et al 2020 and beyond (Shahbazi et al 2016, Popovic et al 2019 will be of particular relevance to improve current PGT-A decision making when only mosaic blastocysts are available. Development and advances in single-cell omics technologies have revolutionized our understanding of cellular heterogeneity and gene expression regulation in health and disease.…”
Section: Human Embryo Development Uncovered By Single-cell Rna-seqmentioning
confidence: 99%